APPLICATION OF A VIBRATING MACHINE FOR RECEIVING AMMONIA WATER FOR PLANT FEEDING - DUSHENKO, OLEKSANDR; TKACHUK, VITALIY (Herald of Khmelnytskyi National University. Technical sciences, 2024)
If high-quality water treatment for boilers is not organized, the impurities present in untreated water lead to a number of problems: large colloidal and mechanical impurities in the form of scale, rust, clay or sand quickly clog the pipes, significantly reducing their internal diameter. This causes the failure of shut-off valves and pumping equipment: hardness salts and other poorly soluble salts (carbonates, magnesium and calcium sulfates, silicates, various compounds of copper and manganese) settle, creating a crust on the metal walls of the equipment, which reduces its heat output. This contributes to a reduction in boiler power, increases energy costs, and significantly shortens the life of the equipment. Based on the analysis of the latest research, it is proposed to improve the quality and composition of water that comes from municipal water supply, artesian wells and reservoirs, before filtering and deaerating water, it is proposed to pre-treat it with hydrocavitation and a magnetic field in order to soften and change its properties. The essence of the operation of the proposed equipment is that the effect of sound hydrocavitation and a variable magnetic field on water is reduced to a single process - the splitting of water molecules in the cavitation cavity into active radicals. The essence of various processes, namely hydrocavitation and magnetic influence on the passage of chemical reactions, breaking of hydrogen bonds in water molecules, is considered. The design of the equipment for the incoming magnetic cavitation preparation of water with an additional hydrocavitation effect on water during the reciprocating movement of the liquid through the nozzle is proposed, which combines the effects of breaking hydrogen bonds in water molecules, oxidation of iron and calcium ions, increasing the Рn indicator, and after its after settling, it is fed to the ion exchange and deaeration units, and later to the heating mains.